Ibrutinib in the treatment of chronic lymphocytic leukemia: 5 years on. Issue 2 (10th December 2019) - Molica, Stefano; Matutes, Estella; Tam, Constantine; Polliack, Aaron
Abstract: A major revolution in the treatment of chronic lymphocytic leukemia (CLL) began with the approval of ibrutinib, a first‐in‐class oral inhibitor of Bruton tyrosine kinase (BTK), for the treatment of relapsed/refractory (R/R) and/or TP53 mutated patients with CLL. However, 5 years later, some issues relating to this disorder still remain including the fact that with ibrutinib only a relatively small proportion of patients achieve complete remission and that ibrutinib‐resistant CLL clones can develop in about 20% of patients. In addition, therapy must still be given continuously, and toxicities leading to drug discontinuation occur in about 30% of patients. In the meantime second‐generation BTK inhibitors have already aroused considerable interest and gathered momentum. A possible strategy to overcome some of these obstacles is to combine ibrutinib with other targeted agents especially in high‐risk disease, such as previously treated refractory patients or those with TP53 aberrations or complex karyotypes, in whom rapid eradication of disease is most desirable. Therapy with single agent ibrutinib should be part of a sequential approach for patients with low risk disease, especially in older patients (aged >70 years) with a higher burden of comorbidities. Long‐term results of ongoing studies combining Ibrutinib with (chemo)‐immunotherapy or other targeted agents are eagerly awaited. Future clinical trials are indeed still needed to provide answers to these open questions.